Prominent alumni / Nichole Heather Esak and Yonina Sikim - Esak, Nichole Heather; Sikim, Yonina (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Prof. Dato Dr Hj Jamil Hj Hamali earned a Diploma in Business Studies from MARA Institute of Technology in Shah Alam in 1984 and a Bachelor of Business Administration (majoring in Industrial Marketing) from Western Michigan University in the United States in 1986. In 1988, he received his MBA with honors from the United States International University in San Diego, USA. Before going to the UK for his Ph.D., he was the Deputy Principal (Academic Affairs) at Universiti Teknologi MARA, Kuching (UiTM).